Pengaruh Metode Latihan Pliometrik dan Metode Gabungan Latihan Pliometrik dengan Keseimbangan terhadap Performa Lay Up Shoot - Fajri, Ilham Truly; Hidayah, Nida'ul (Jurnal Kepelatihan Olahraga, 2021)
This research discusses the effect of plyometric training method and combined plyometric and balance training method on lay up shoot performance. Lay up shoot is the easiest way to shoot the ball to the ring because this kind of shoot used as close as possible to the ring. The purpose of this research is to determine "The effect of plyometric training method and combined plyometric and balance training method on lay up shoot performance". This research method used experimental method. The population used in this research is male UPI basketball athletes. The samples that researcher used is total sampling technique i.e 16 male UPI basketball athletes. The instrument used is the Lay Up Test. The result of this research showed that is a significant impact between plyometric training method and combined plyometric and balance training method on lay up shoot performance male UPI basketball athletes.